A multi-dynamic generalized expenditure system of the demand for consumer goods - Gamaletsos, Theodore (SPOUDAI Journal of Economics and Business, 2008)
The dynamic form of the GLES model, the DGLES model, has been presented by the author at the International Econometic Society European Meeting in 1979 and is published in the Proceedings of the Econometric Society European Meeting 1979 (Selected Econometric Papers in Memory of Stefan Valavanis) by North-Holland, chapter 17 pp. 379-389. In this article I will present a more dynamic form of the DGLES model which I call Multi- Dynamic Generalized Linear Expenditure System, in short MDGLES model, in which will not destroy the basic (classical) properties of the previous GLES and DGLES models. For better understanding of the presentation of the MDGLES model I will first present the DGLES upon which is based the MDGLES model.